Study on thermophysical properties of fluids containing carbon nanotubes / Rad Sadri - Rad, Sadri (2013)
In the verge of acute energy demand the heat transfer fluids were required to modify and develop a high performance liquid as nanofluid. The properties of the fluids are not yet fully obtained. The carbon nanotubes (CNT`s) are able to enhance the thermal performance of the conventional heat transfer liquids, nonetheless the majority of past works have been focused on the impacts of concentrations of carbon nanotubes on the thermo-physical properties of the nanofluids. No considerable researches have been performed to straightly indicate the influence of preparation methods on stability, thermal conductivity and viscosity of carbon nanotubes suspensions. The thermo-physical properties of CNT` nanofluids differ under different preparation techniques and the precise measurements were performed in this current experiment to figure out the impacts of these methods. The effect of variation of ultrasonication time and different surfactants on the thermal properties of Multi-walled carbon nanotubes(MWCNT`s) were studied. The thermo-physical properties measured were thermal conductivity and viscosity under different temperatures. Gum Arabic (GA), Sodium dodecylbenzenesulfonate (SDBS) and Sodium dodecyl sulfate (SDS) were used as surfactants. Addition of GA showed superior thermal conductivity of nanofluids than that of SDBS and SDS dispersants in it. Samples of 0.5 wt% MWCNT, 0.25% GA and distilled water as the base liquid were prepared at different ultrasonication times in this study. Imaging was carried out by TEM technique to view the dispersing characteristics of samples and observed both the reduction of CNT agglomerations and length. The reduction in agglomerations was found to be more important than that of CNT length. The results exhibited that the ultrasonication affects thermal conductivity, viscosity and dispersion. The maximum thermal conductivity enhancement was found to be 22.31% (the ratio of 1.22) at 45 o C temperature of the sample sonication bath for 200 minutes. The thermal conductivity enhanced with the increase of both temperature and sonication time. In the consideration of viscosity, the nanofluids treated as shear thinning and non-Newtonian fluids. The viscosity was raised to the maximum for the sample sonication of 50 minutes and the subsequently decreased with the further increase of sonication time. Thus the lowest viscosity and the highest thermal conductivity ratios were achieved by utilizing prolonged sonication time, which could be useful in heat transfer applications.